Validitas Video Pembelajaran dengan Aplikasi Capcut pada Materi Sholat Kelas VII - Alamsyah, Alamsyah; Maulana, Andin Muhammad (Lembaga Yasin AlSys, 2024)
The validation process is needed to ensure that the learning video has quality and accuracy in delivering the material. This study focuses on developing an animated video about prayer practice aimed at class VII students, utilizing the Capcut application as a creation tool. The method used is Research and Development (R&D) with a 4D approach which only includes three stages, namely: Define, Design and Development. Video quality validation was carried out by four experts, consisting of two material experts and two media experts. The assessment results show that the video obtained an average score of 133 with a feasibility percentage reaching 73%, indicating that this media is very suitable for use in learning as an interesting and effective tool.